2008
DOI: 10.1142/9789812818829_0010
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Dewetting of Thin Liquid Films

Abstract: The stability of thin liquid coatings is of fundamental interest in everyday life. Homogeneous and non-volatile liquid coatings may dewet either by heterogeneous nucleation, thermal nucleation, or spinodal dewetting. Wetting and dewetting is explained on a fundamental level, including a discussion of relevant interactions. This chapter will also address the various dewetting scenarios and explain how the effective interface potential governs the behavior obtained for various stratified substrates and film thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 66 publications
2
41
0
Order By: Relevance
“…Previous experiments, indeed, identified a significant influence of the longrange component of the interaction potential on the dewetting of thin liquid films [6,7], their liquid front profiles [8,9] and the mesoscopic organization of magnetic nanocrystals [10]. Recently, a similar influence was detected on the adsorption kinetics of proteins [11][12][13] and the adhesion of bacteria [14].…”
Section: Introductionmentioning
confidence: 83%
“…Previous experiments, indeed, identified a significant influence of the longrange component of the interaction potential on the dewetting of thin liquid films [6,7], their liquid front profiles [8,9] and the mesoscopic organization of magnetic nanocrystals [10]. Recently, a similar influence was detected on the adsorption kinetics of proteins [11][12][13] and the adhesion of bacteria [14].…”
Section: Introductionmentioning
confidence: 83%
“…We have mentioned that physical experiments have shown that a nearly uniform layer of a thin film will break up due to instabilities [2,6]. Our first step will be to try to model this dewetting.…”
Section: Formulation Of the Thin Film Problemmentioning
confidence: 99%
“…This particular phenomenon is called dewetting, and it occurs frequently in dynamic mechanical systems. For example, experiments on different polymer solutions [2,6] have attempted to pin down the peculiar nature of dewetting. More simply however, this behavior is also exhibited in everyday materials such as printing ink, paint, and lubricant.…”
Section: Introductionmentioning
confidence: 99%
“…Returning to the discussion of thin films, we note that such films are often unstable due to destabilizing liquid-solid interaction forces. The nature of these instabilities has been considered extensively in a variety of settings including polymer films [8,18,19], liquid crystal films [20][21][22], as well as liquid metals [23,24] (see also [25,26] for excellent reviews of this topic). The instability development leads to many questions even in relatively simple settings.…”
mentioning
confidence: 99%
“…We will focus on particular examples of nematic liquid crystal films and, to a smaller extent, on polymer films; however, the main features of our results are general, and will be of relevance to a number of problems involving thin films. What distinguishes different films, substrates and film thickness regimes, at least for slow evolution where inertial effects are not significant, is essentially the form of (effective) disjoining pressure that, in addition to liquid/solid interaction, may include the effects of anchoring in the context of liquid crystals; interactions of electric or magnetic type in the context of ferrofluids [29]; or composite substrates in the case of polymer films [18]. The influence of the functional form of such effective disjoining pressure on film stability was discussed in two spatial dimensions (2D) recently [28].…”
mentioning
confidence: 99%